2003
DOI: 10.1046/j.1365-2605.2003.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

CAG repeat length in the androgen receptor gene affects the risk of male infertility

Abstract: During recent years several studies have suggested that a slight increase in the number of CAG repeat sequences in exon 1 of the androgen receptor gene causes idiopathic oligozoospermia. We tested whether CAG repeats are more numerous in men with idiopathic infertility compared to those with known causes of oligozoospermia. CAG repeats were analysed in a consecutive sample of 217 infertile men covering a wide range of diagnoses and sperm counts. Data were compared with those of a control group of 131 normozoos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Despite promising in-vitro data, the initial observations of a significant association between relatively long CAG repeats and Symposium -Mutations and spermatogenesis -F Nuti & C Krausz impaired sperm production (Dowsing et al, 1999) have not been confirmed by subsequent studies (for review see Asatiani et al, 2003). Similarly, it is still under question whether the (GGC) n repeat has a pathogenic role in abnormal spermatogenesis (see Krausz and Giachini, 2007).…”
Section: Steroid Receptor Gene Mutationsmentioning
confidence: 99%
“…Despite promising in-vitro data, the initial observations of a significant association between relatively long CAG repeats and Symposium -Mutations and spermatogenesis -F Nuti & C Krausz impaired sperm production (Dowsing et al, 1999) have not been confirmed by subsequent studies (for review see Asatiani et al, 2003). Similarly, it is still under question whether the (GGC) n repeat has a pathogenic role in abnormal spermatogenesis (see Krausz and Giachini, 2007).…”
Section: Steroid Receptor Gene Mutationsmentioning
confidence: 99%
“…male infertility, hypogonadism, gynecomastia, cryptorchidism, etc.). For example, some studies have shown the presence of larger CAG repeat size in the AR gene of infertile men with extremely severe oligozoospermia [34] and azoospermia [35]; other studies failed to demonstrated a direct correlation between long CAG triplet repeats and semen parameter found abnormal in oligozoospermia, but it has been proposed that the CAG repeats might allow the development of infertility in response to any pathogen/epigenetic factors [36]. Some other studies have associated the increased CAG triplet repeat size in AR with fat-free mass in men [37], while contrasting results have been obtained on the link with depression in middle-aged [38] or elderly [39] men.…”
Section: The Ar Polygln Polymorphism In Endocrine-related Diseasesmentioning
confidence: 99%
“…However, the Chinese study found an association between CAG repeat length and depressed spermatogenesis in an azoospermic subgroup only but not in a severely oligozoospermic group of patients. The most recent CAG expansion publications have reported no link between CAG repeat polymorphisms and male infertility in Israeli, German, Indian, Finnish, and Italian populations (Asatiani et al, 2003;Dhillon & Husain, 2003;Lund et al, 2003;Ferlin et al, 2004;Milatiner et al, 2004). The Israeli study did, however, demonstrate an association between CAG repeat length and a teratozoospermic (<30% with normal forms) subgroup.…”
Section: Discussionmentioning
confidence: 83%